1972
DOI: 10.1073/pnas.69.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Light Chain Sequences of Human IgM Cold Agglutinins

Abstract: The amino-terminal amino-acid sequence has been determined for the kappa light chains of nine IgM cold agglutinins with specificity for blood grouprelated carbohydrate antigens. Six of the nine sequences corresponded to the prototype VKIII subgroup pattern, two to that of subgroup VKII, and only one to the VKI subgroup. This distribution of kappa subgroups differs markedly from that of normal and myeloma proteins sequenced to date, where the VKI subgroup is more prevalent than either VKii or VKiii. Evidence is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

1973
1973
1979
1979

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(19 citation statements)
references
References 35 publications
0
18
1
Order By: Relevance
“…In the case of specific antibodies an association to antibody specificity has been demonstrated serologically in the VK system (22,27). Limited sequence studies have indicated a restriction of certain antibody population to given V subgroups (28,29). The present serological typing procedure should aid considerably in verifying and extending these associations.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of specific antibodies an association to antibody specificity has been demonstrated serologically in the VK system (22,27). Limited sequence studies have indicated a restriction of certain antibody population to given V subgroups (28,29). The present serological typing procedure should aid considerably in verifying and extending these associations.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the most pertinent to the present study, since they arose in genetically different individuals, are the human monoclonal cold agglutinins and antigamma globulins studied by Kunkel, Capra, and their colleagues (44,45) . Though no data on heavy chain structure have been presented, amino acid sequence analysis of the light chains from 6 of 10 cold agglutinins showed minimal differences among them (46) . Likewise, antigamma globulins selected for similarity in shared idiotypic determinants exhibit remarkable structural similarities in either their light or their heavy chains (47) .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in some, but not all strains of mice, antibodies produced to a-l,3-1inked dextrans (27)(28) or PC (6, 7) exhibit cross-idiotypic specificity and in the former response, the idiotypic specificity appears to be site related (29). Cross-idiotypic specificity also exists within groups of myeloma proteins with similar specificities (30)(31)(32), and in some of these systems as well as others, structure-function (33)(34)(35) or idiotype-function (29,36) relationships are currently being delineated. Among the human IgM proteins with anti-'g-globulin activity which have been extensively studied by Kunkel and his colleagues, two major groups appear which are classified on the basis of shared idiotypic determinants (32).…”
Section: Extent Of Shared Idiotypy On Hopc 8 and Mouse Anti-pc Antibomentioning
confidence: 99%